Renewable Energy Supply Shocks from Wind Electricity - Paula Patzelt (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper identifies electricity supply shocks by exploiting the fact that variations in wind speed at turbine locations are exogenous with respect to macroeconomic outcomes and drive electricity prices in European wholesale markets inframarginally. Instrumenting electricity price changes with these wind supply shocks, I find that higher electricity prices raise inflation and reduce electricity use as expected, but generate surprising effects on economic activity. Unemployment rises, but industrial production also rises over time, and the effect on GDP is negligible. As these effects differ markedly from the impact of oil price shocks, they suggest that as economies shift from fossil fuels to renewable electricity, business cycle dynamics may persistently change.
Keywords: E31; E32; Q42; Q43; 330; business cycle; prices; energy supply; energy shocks; wind energy